Physical Fitness of Cleaners in Faculty of Medicine Universitas Padjadjaran, November 2012 - Sulistijo, Adi Wibisono; Purba, Ambrosius; Pandji, Tri Damiati (Althea Medical Journal, 2015)
Background: Cleaning is an occupation that is carried out worldwide in many different environments. Cleaning workers (cleaners) often have low occupational skills and belong to the less advantaged educational and socioeconomic groups. Because of the high physical work demands and low cardiorespiratory fitness, cleaners have the risk to have cardiovascular diseases. The aim of this study was to measure the 5 components of physical fitness (cardiorespiratory endurance, muscle endurance, muscle strength, flexibility and body composition) of cleaners in Faculty of Medicine Universitas Padjadjaran.Methods: A descriptive study was carried out to all cleaners (31 persons) of Faculty of Medicine Universitas Padjadjaran in November 2012. The subjects were tested for cardiorespiratory endurance, muscle endurance, muscle strength, flexibility and body composition. The results were categorized using the standard of Ministry of Health Republic Indonesia.Results: From 31 subjects, cardiorespiratory endurance was in poor category (50%). Shoulder and hand muscle endurance was in poor category (54.8%) and stomach muscle endurance was in very poor category (67.7%). Handâgrip muscular strength was in very poor category: right hand (80.7%) and left hand (87.1%). Back muscle strength was in poor category (58.1%). Leg muscular strength was in very poor category (48.4%). Flexibility was in a very good category (97%) and body composition was also in a good category (54.8%).Conclusions: From 5 components of cleanersâ physical fitness, 3 components (cardiorespiratory endurance, muscle endurance and muscular strength) are in poor and very poor category.Â DOI:Â 10.15850/amj.v2n3.504